(untitled) (Colombia Medica, 1993)
This article describes a family strategy for the generic prevention of drug abuse and other deviant behaviors. The strategy was carried out through 10 sessions, 2 hours each, in participatory experimental groups. Several families (parents and their adolescent children from the eighth grade of a private middle-class school in Cali, Colombia) participated in the discussion of different aspects of communication, sexuality, values, and risk factors associated with drug abuse as they related to their own family life. Various standardized instruments were utilized for the process evaluation and the evaluation of the immediate impact of such sessions; some of the instruments did not show significant statistical differences, mainly because the group was relatively small. The final impression and the review of the Opinion Questionnaire showed that the majority of the participants found the sessions beneficial; for all of them, this was the first opportunity to discuss, as a family, fundamental themes in their lives. An additional benefit mentioned by most partici-pants was to have experienced how many families considered mild what for others was taken as extremely serious. Shared experiential group difficulties with other families and realizing how complex problems were dealt with naturally helped parents to decrease the tragic intensity they used to evaluate their children’s future.